Modele edukacji artystycznej. Skąd i dokąd - Jenčuráková, Eva; Tomaschová, Lucia (Warstwy, 2021)
The title of the article is identical with the title of the international conference held by the Department of Theory and History of Art, Faculty of Arts, Technical University of Košice, Slovakia. The conference took place on 5 and 6 October 2018 to mark the 20th anniversary of the faculty. Over the period of two days, 26 speakers including theoreticians, teachers, artists, and art school graduates presented various models of art. education, and raised many profound questions about the role of art schools in society.